A novel portable and radiation-free method for assessing scoliosis: an accurate and reproducible study - Hui Wang; Yunfeng Zhu; Qiyuan Bao; Yong Lu; Fuhua Yan; Lianjun Du; Le Qin (BMC Musculoskeletal Disorders, 2025)
Abstract Background This study aimed to evaluate the accuracy and reproducibility of a newly developed portable and radiation-free three-dimensional spine sensing system (3D-SSS) for scoliosis assessment. Methods A total of 145 patients underwent full-spine imaging using the EOS imaging system, and 3D-SSS data were collected between February 2023 and April 2023. A radiologist used sterEOS software to reconstruct the spine in 3D and obtain the Cobb angle. One radiologist and one orthopedist independently measured the patients using 3D-SSS, with the orthopedist performing two measurements per patient. The 3D-SSS post-processing system automatically generated the Cobb angle. Results The mean Cobb angles obtained from EOS and 3D-SSS were 13.7 ± 9.9° (0.5∽45.7°) and 12.5 ± 8.6° (0.4∽40°), respectively. The intraclass correlation coefficient (ICC) for reliability between EOS and 3D-SSS was 0.921, indicating excellent agreement. Bland–Altman analysis revealed a bias of -1.171° between EOS and 3D-SSS, with only 10 patients outside the limits of agreement (-8.3∽6.0°). The root mean square error between EOS and 3D-SSS was 3.2°. A strong correlation was observed between the Cobb angles measured by EOS and 3D-SSS (r = 0.931, P < 0.001). The receiver operating characteristics curve showed that the diagnostic performance of 3D-SSS for scoliosis was 0.953 (P < 0.001). The sensitivity, specificity, positive predictive value, and negative predictive value of 3D-SSS for diagnosing scoliosis were 87.8%, 92.1%, 93.5%, and 85.3%, respectively. The intraobserver and interobserver ICCs for Cobb angles derived from 3D-SSS were 0.969 and 0.934, respectively, demonstrating excellent reproducibility. Conclusions The portable and radiation-free 3D-SSS accurately measured scoliosis and provided highly reproducible data. This system offers a novel method for clinicians to screen and monitor scoliosis in young patients.